Runaway Dynamics in Reactor-Scale Spherical Tokamak Disruptions - Berger, Esmée (My University, 2022)
One of the most promising concepts to achieve commercial fusion power, to date, is a toroidal magnetic confinement system centred around a tokamak. To aid the development, compact spherical tokamaks have long been proposed as component testing facilities. There is also an effort to design and construct spherical tokamaks suitable for energy production, with an example being the STEP program in the UK. One of the remaining obstacles for all reactor-scale tokamaks is so-called runaway electrons — electrons accelerated to relativistic speeds. These can be generated during disruptions, which are off-normal events where the confinement of the plasma is rapidly lost. As runaway electrons can severely damage the machine walls, their production and mitigation has been extensively studied for conventional tokamaks. However, due to the disruption dynamics typically being different in spherical tokamaks, the existing results cannot directly be transferred to these more compact devices. Therefore, runaway dynamics in reactor-scale spherical tokamaks is investigated in this work. We consider both the severity of runaway generation during unmitigated disruptions, as well as the effect that typical mitigation schemes based on massive material injection have on runaway production. The study is conducted using the numerical framework DREAM (Disruption Runaway Electron Analysis Model) and we find that, in many cases, mitigation strategies are necessary if the runaway current is to be prevented from reaching multi-megaampere levels. Our results indicate that with a suitably chosen deuterium-neon mixture for mitigation, it is possible to achieve a tolerable runaway current and ohmic current evolution. With such parameters, however, the majority of the thermal energy loss happens through radial transport rather than radiation, which poses a risk of unacceptable localised heat loads.
Keywords: fusion plasma; spherical tokamak; runaway electron; disruption mitigation; material injection